Improving the library space of the Philippine School of Interior Design using design charrette - Laluna, Jennifer J. (2018)
With the Philippine School of Interior Design curriculum' fortification and enhancement of its facilities prompted a need for a library to improve as a place to study that would cope with the students' learning needs. It is in this light that this study focused on how the physical library can be structured, arranged and improved by the important school stakeholders. Due to participatory focus, two groups utilized design charrette method to analyze the data gathered from the semi-structured interview, group discussions, and group reporting. Content and thematic analysis was done to describe and interpret the participants' views in the stages of the activity.